Controlling the Structure, Properties and Surface Reactivity of Clickable Azide‐Functionalized Au25(SR)18 Nanocluster Platforms Through Regioisomeric Ligand Modifications. Issue 29 (1st June 2022) - Gunawardene, Praveen N.; Martin, Julia; Wong, Jonathan M.; Ding, Zhifeng; Corrigan, John F.; Workentin, Mark S.
Abstract: To fine‐tune structure–property correlations of thiolate‐protected gold nanoclusters through post‐assembly surface modifications, we report the synthesis of the o, m, and p regioisomeric forms of the anionic azide‐functionalized [Au25 (SCH2 CH2 ‐C6 H4 ‐N3 )18 ] 1− platform. They can undergo cluster–surface strain‐promoted alkyne–azide cycloaddition ( CS ‐SPAAC) chemistry with complementary strained‐alkynes. Although their optical properties are similar, the electrochemical properties appear to correlate with the position of the azido group. The ability to conduct CS ‐SPAAC chemistry without altering the parent nanocluster structure is different as the isomeric form of the surface ligand is changed, with the [Au25 (SCH2 CH2 ‐ p ‐C6 H4 ‐N3 )18 ] 1− isomer having the highest reaction rates, while the [Au25 (SCH2 CH2 ‐ o ‐C6 H4 ‐N3 )18 ] 1− isomer is not stable following CS ‐SPAAC. Single‐crystal X‐ray diffraction provide the molecular structure of the neutral forms of the three regioisomeric clusters, [Au25 (SCH2 CH2 ‐ o / m / p ‐C6 H4 ‐N3 ] 0, which illustrates correlated structural features of the central core as the position of the azido moiety is changed. Abstract : The correlational properties of regioisomeric, azide‐functionalized Au25 (SR)18 nanoclusters have been explored, and the molecular structures of the neutral forms of these clusters have been obtained. Although the optical properties are similar, alterations to electrochemical profiles and cluster–surface reactivity with a strained‐alkyne have been observed that appear to change as the position of the surface azido moiety is changed.